Heart rate variability and target organ damage in hypertensive patients - Melillo, Paolo; Izzo, Raffaele; De Luca, Nicola; Pecchia, Leandro (BioMed Central, 2012)
Background We evaluated the association between linear standard Heart Rate Variability (HRV) measures and vascular, renal and cardiac target organ damage (TOD).